Phospholipase D signaling modulates the inflammatory response during 6-OH dopamine (6-OHDA)-induced neurotoxicity - Iglesias González, Pablo Andrés (2017)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder related with aging. The death of dopaminergic neurons triggered by oxidative stress and mitochondrial dysfunction is one pathognomonic characteristic of PD patients. Neuronal exposure to 6-OH dopamine (6-OHDA), a hydroxylated analogue of dopamine, constitutes a very useful strategy for studying the molecular events associated with neuronal death in PD. Our aim in this study was to characterize the role of phospholipase D (PLD) signaling during 6-OHDA-induced neurotoxicity. The exposure to 6-OHDA (50 and 75 µM) induced an increase in reactive oxygen species (p<0.05) and lactate dehydrogenase release (p<0.05) along with a decrease in mitochondrial viability (p< 0.001) in human neuroblastoma IMR-32 cells. We also observed by immunocytochemistry (p<0.05) and subcellular fractionation followed by Western blot (p<0.01) the nuclear translocation of NF-κB p65 subunit (p<0.01) in the presence of 6-OHDA (50 µM). NF-κB nuclear localization was also accompanied by an increase of IkB phosphorylation (p<0.05) as well as COX-2 mRNA levels (determined by RT-qPCR, p<0.001). On the other hand, pharmacological inhibition of PLD1 (EVJ, 5µM) and PLD2 (APV, 5 µM) was able to prevent the decrease in cell viability triggered by 6-OHDA (p < 0.01; p<0.001). In line with this, pharmacological inhibition of PLD1 with EVJ inhibited NF-κB p65 subunit nuclear translocation (p < 0.001). Our results indicate that oxidative stress induced by 6-OHDA triggers an inflammatory response that involves NF-κB activation and COX-2 upregulation. Moreover, we also demonstrate here that phosphatidic acid signaling elicited by PLD modulates the inflammatory response associated with neuronal injury.